Effect of Seed Priming on Field Emergence and Yield in Different Bitter Gourd Cultivars (Momordica charantia L.) Under Sub-Optimal Temperature - RAJINDER SINGH; RAKESH KUMAR (Seed Research, 2026)
The present investigation was carried at Vegetable Research Farm of Department of Vegetable Science, PAU Ludhiana. The experiment was laid in split plot design with five genotypes (Punjab 14, Punjab Kareli, Jaunpuri Long, Katahi and Green Special Long) in main plot and six treatments along with control (hydration for 24 hours, GA3 @ 100 ppm for 24 hours, KNO3 @ 100 ppm for 24 hours, KH₂PO, @ 10 M for 24 hours, hydration for 24 hours and buried in FYM for 1 day, hydration for 24 hours and buried in FYM for 2 days) in sub plot. Seeds were sown in polythene bags during third week of January 2012. The results revealed that pre sowing treatment with GA, @ 100 ppm for 24 hours resulted in maximum germination (%), field emergence, speed of emergence, vine length, days to first harvest, number of fruits per plant and yield per plant. Among various genotypes tested, cultivars Katahi, Punjab 14 and Jaunpuri Long responded better to seed priming treatments than other cultivars.